Hypertrophic Olivary Degeneration and Holmes' Tremor Secondary to Bleeding of Cavernous Malformation in the Midbrain. (8th October 2014) - Menéndez, Djalma F. S.; Cury, Rubens G.; Barbosa, Egberto R.; Teixeira, Manoel J.; Fonoff, Erich T.
Background: Hypertrophic olivary degeneration (HOD) is a rare phenomenon, probably related to transsynaptic degeneration of the inferior olivary nucleus. It usually occurs as a response to primary injury of dento-rubro-olivary pathways. Case report: A young man developed Holmes' tremor 7 months after a cavernous malformation bleed in the midbrain. Typical findings of HOD were observed in the magnetic resonance images: bilateral and asymmetric hypertrophy of the olivary nucleus with slight hypersignal in T2-weighted images. Because of the striking disability related to drug-resistant tremor, the patient underwent stereotactic thalamotomy (nucleus ventralis intermedius of the thalamus/zona incerta) with pronounced functional improvement over time. Discussion: Disruption of circuits in the Guillain–Mollaret triangle classically results in palatal myoclonus, however midbrain (Holmes') tremor can also occur, as we now describe.